Respostas
respondido por:
7
Oi Barbara
logm(2) = a
log(2)/log(m) = a
log(2) = a*log(m)
log(3)/log(m) = b
log(3) = b*log(m)
logm(7) = c
log(7)/log(m) = c
log(7) = c*log(m)
64/(2.1*60) = 32/63
log(32) = log(2^5) = 5log(2) = 5alog(m)
log(63) = log(9) + log(7) = 2log(3) + log(7)
log(63) = 2b*log(m) + c*log(m)
log(32/63) = 5alog(m) - 2b*log(m) - c*log(m)
log(32/63) = log(m)*(5a - 2b - c)
logm(2) = a
log(2)/log(m) = a
log(2) = a*log(m)
log(3)/log(m) = b
log(3) = b*log(m)
logm(7) = c
log(7)/log(m) = c
log(7) = c*log(m)
64/(2.1*60) = 32/63
log(32) = log(2^5) = 5log(2) = 5alog(m)
log(63) = log(9) + log(7) = 2log(3) + log(7)
log(63) = 2b*log(m) + c*log(m)
log(32/63) = 5alog(m) - 2b*log(m) - c*log(m)
log(32/63) = log(m)*(5a - 2b - c)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás